English letters and Indian literacies : reading, writing, and New England missionary schools, 1750-1830 - Wyss, Hilary E. (Haney Foundation series., 2012)
Focusing on boarding schools established by New England missionaries, English Letters and Indian Literacies explores the ways Native students negotiated the variety of pedagogical practices and technologies of literacy and managed those technologies for their own ends.